Epidemiology of Canine Vector-Borne Pathogens (CVBPs) of Dogs in Nigerian Communities - Apaa, Ternenge; Tarlinton, Rachael; Dunham, Stephen (2022)
Canine vector-borne pathogens (CVBPs) have a significant impact on the health and welfare of dogs and humans. There is extremely little data on the prevalence of tick species, CVBPs and their impact on Nigerian dogs. The main aim of this study was to identify ticks, CVBPs and associated risk factors in Nigerian dogs using point-of-care (POC) test, PCR, metagenomics profiling and multivariate modelling. A total of 259 canine blood and 122 hard tick samples were examined in this study. POC and PCR-based tests showed that Borrelia burgdorferi is unlikely to be present in Nigerian dogs, while an unexpectedly low prevalence of Dirofilaria immitis was reported. The low prevalence of Anaplasma species and high prevalence of Ehrlichia canis was reported via both POC and PCR test. While high prevalence of Babesia species (B. vogeli and B. rossi) were reported via PCR test on canine blood, this report confirmed the absence of B. gibsoni, B. canis and B. vulpes in canine blood sample examined. Risk factor analysis using PCR results showed that exotic dogs were more likely to test positive to CVBPs during the rainy season. While risk factors analysis from the POC test results showed that older and tick infested dogs were more likely to test positive to CVBPs, implying that older dogs would have a higher lifetime exposure risk than younger dogs. An increased risk of tick infestation was reported in male dogs which may be due to increased roaming activities. The tropical lineage of Rhipicephalus sanguineus (s.l.) and Haemaphysalis leachi were the most prevalent tick species infesting dogs, while Haemaphysalis spp. tentatively identified as H. longicornis were demonstrated to infest Gallus domesticus. Metagenomics profiling of ticks indicated the presence of Leishmania, Plasmodium, Ehrlichia, Anaplasma and Candidatus Coxiella species, demonstrating the risk of canine disease burden and human zoonosis. While additional studies are required to confirm these reports, the inclusion of these pathogens in differential diagnosis during clinical examination of dogs, and adherence to strategic tick control is recommended.